OPTIMIZING SSCM IN THE SUPPLY CHAIN OF TRASH FISH TYPE TUNA USING RAPFISH IN COASTAL PASURUAN - Misbah, Achmad; Sucipto, Sucipto; Asmaul Mustaniroh, Siti; Santoso, imam (Fakultas Teknologi Pertanian Universitas Brawijaya, 2025)
This study aims to optimize the sustainable supply chain management (SSCM) model for tuna trash fish in the coastal area of Pasuruan by involving three leading actors in the supply chain: fishermen, collectors, and processing businesses. The approach method used is the Rapid Appraisal for Fisheries (RAPFISH), based on Multidimensional Scaling (MDS), to evaluate the level of sustainability across environmental, social, and economic dimensions. The results show that collectors are in the fairly sustainable category (73.50%), while fishermen (55.62%) and Micro enterprise of trash fish type tuna (55.27%) are at the lower limit of the same category. The main levers for each actor include occupational safety, labor cost efficiency, and working environment conditions. The main conclusion states that the sustainability of the tuna supply chain still requires cross-dimensional improvements. The implications of these results underscore the importance of targeted actor capacity-building strategies, such as occupational safety training for fishermen, digitizing collector administration, and enhancing consumer services in micro enterprises of trash fish type Tuna, as well as opening up opportunities for further research based on an integrative approach to support long-term sustainability.